Structure and Function: impact on Employment of Women in Law Enforcement - Matusiak, Randa Embry (Women & criminal justice, 2018)
Although women experienced a marked increase in representation as full-time sworn law enforcement officers during the 1980s and 1990s, growth has slowed in recent years and women continue to be underrepresented in the profession. Employing multiple waves of Law Enforcement Management and Administrative Statistics data, this study describes trends in representation of women in policing and explores their continued lack of representation to determine whether organizational variables (structure and function) work to support a hegemonic masculinity and whether those structures are malleable over time. Results from a series of ordinary least squares regression models indicate several structural impediments to women in policing, but these are not consistent barriers.